2006
DOI: 10.1111/j.1540-8175.2006.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Atropine as a Chronotropic Agent in Heart Transplant Patients Undergoing Dobutamine Stress Echocardiography

Abstract: The adjunctive use of atropine in HTX patients during DSE aids in reaching 85% of maximum predicted HR in some patients. Furthermore, resting HR may predict the additional need of atropine during DSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Furthermore, we observed substantial effects even with a very low dose of atropine (0.2 mg/kg twice daily for 7 days; Fig. 1 C-F), which was the same or less than the doses used in most studies of muscarinic signaling (Molinengo et al, 1989; Kociolek et al, 2006). Lastly, when we applied atropine at the lowest dose (0.2mg/kg once-daily for only 5 days; n=6 mice), we found milder defects that were confined to the synaptic area, and both preterminal axons and myelinating Schwann cells appeared completely normal (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, we observed substantial effects even with a very low dose of atropine (0.2 mg/kg twice daily for 7 days; Fig. 1 C-F), which was the same or less than the doses used in most studies of muscarinic signaling (Molinengo et al, 1989; Kociolek et al, 2006). Lastly, when we applied atropine at the lowest dose (0.2mg/kg once-daily for only 5 days; n=6 mice), we found milder defects that were confined to the synaptic area, and both preterminal axons and myelinating Schwann cells appeared completely normal (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 70%
“…These dramatic effects were unexpected because atropine is commonly used in the clinic (Das, 1989; Kociolek et al, 2006). The effects are unlikely to be indirect or due to overdosage.…”
Section: Discussionmentioning
confidence: 99%
“…4) We used the functional consequences of reinnervation (HR response to exercise) to infer reinnervation. This technique assesses sympathetic reinnervation only, and autonomic regulation involving parasympathetic and sympathetic innervation may be more accurately inferred from dobutamine stress testing with atropine (26). Additionally, there is direct evidence that reinnervation of the heart occurs after transplantation in animals (34), and there is growing evidence from clinical (40), physiological (3,8), and biochemical (2,24) studies in humans that partial reinnervation may occur at least 1 yr after transplantation.…”
Section: Ventricular-vascular Coupling and V O 2 In Htrmentioning
confidence: 99%
“…5,11,1417 A retrospective study by Kociolek et al included 21 transplant patients who received atropine during DSE, and a similar study by Flox et al included 14 transplant patients who also received both agents. 11,16 The patient populations in those studies were similar to ours, though the study by Flox et al did not include patients using beta-blockers. Although there were slight protocol differences, such as higher doses of atropine and dobutamine in the study by Kociolek et al, no adverse events were reported in either study.…”
Section: Discussionmentioning
confidence: 59%
“…11,16 This difference could be due in part to protocol differences such as the maximum doses of dobutamine and atropine that were given. Doses of dobutamine and atropine for each patient in our study were determined by the supervising physician.…”
Section: Discussionmentioning
confidence: 99%